Preventing Medication Errors - Institute of Medicine (The National Academies Press, 2007)
In 1996 the Institute of Medicine launched the Quality Chasm Series, a series of reports focused on assessing and improving the nation's quality of health care. Preventing Medication Errors is the newest volume in the series. Responding to the key messages in earlier volumes of the series—To Err Is Human (2000), Crossing the Quality Chasm (2001), and Patient Safety (2004)—this book sets forth an agenda for improving the safety of medication use. It begins by providing an overview of the system for drug development, regulation, distribution, and use. Preventing Medication Errors also examines the peer-reviewed literature on the incidence and the cost of medication errors and the effectiveness of error prevention strategies. Presenting data that will foster the reduction of medication errors, the book provides action agendas detailing the measures needed to improve the safety of medication use in both the short- and long-term. Patients, primary health care providers, health care organizations, purchasers of group health care, legislators, and those affiliated with providing medications and medication- related products and services will benefit from this guide to reducing medication errors.
Keywords: Health and Medicine

Patient Safety: Achieving a New Standard for Care - Institute of Medicine (The National Academies Press, 2004)
Americans should be able to count on receiving health care that is safe. To achieve this, a new health care delivery system is needed — a system that both prevents errors from occurring, and learns from them when they do occur. The development of such a system requires a commitment by all stakeholders to a culture of safety and to the development of improved information systems for the delivery of health care. This national health information infrastructure is needed to provide immediate access to complete patient information and decision-support tools for clinicians and their patients. In addition, this infrastructure must capture patient safety information as a by-product of care and use this information to design even safer delivery systems. Health data standards are both a critical and time-sensitive building block of the national health information infrastructure. Building on the Institute of Medicine reports To Err Is Human and Crossing the Quality Chasm, Patient Safety puts forward a road map for the development and adoption of key health care data standards to support both information exchange and the reporting and analysis of patient safety data.
Keywords: Health and Medicine

Improving Diagnosis in Health Care - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
Getting the right diagnosis is a key aspect of health care - it provides an explanation of a patient's health problem and informs subsequent health care decisions. The diagnostic process is a complex, collaborative activity that involves clinical reasoning and information gathering to determine a patient's health problem. According to Improving Diagnosis in Health Care, diagnostic errors-inaccurate or delayed diagnoses-persist throughout all settings of care and continue to harm an unacceptable number of patients. It is likely that most people will experience at least one diagnostic error in their lifetime, sometimes with devastating consequences. Diagnostic errors may cause harm to patients by preventing or delaying appropriate treatment, providing unnecessary or harmful treatment, or resulting in psychological or financial repercussions. The committee concluded that improving the diagnostic process is not only possible, but also represents a moral, professional, and public health imperative. Improving Diagnosis in Health Care, a continuation of the landmark Institute of Medicine reports To Err Is Human (2000) and Crossing the Quality Chasm (2001), finds that diagnosis-and, in particular, the occurrence of diagnostic errors—has been largely unappreciated in efforts to improve the quality and safety of health care. Without a dedicated focus on improving diagnosis, diagnostic errors will likely worsen as the delivery of health care and the diagnostic process continue to increase in complexity. Just as the diagnostic process is a collaborative activity, improving diagnosis will require collaboration and a widespread commitment to change among health care professionals, health care organizations, patients and their families, researchers, and policy makers. The recommendations of Improving Diagnosis in Health Care contribute to the growing momentum for change in this crucial area of health care quality and safety.
Keywords: Health and Medicine

Priority Areas for National Action: Transforming Health Care Quality - Institute of Medicine (The National Academies Press, 2003)
A new release in the Quality Chasm Series, Priority Areas for National Action recommends a set of 20 priority areas that the U.S. Department of Health and Human Services and other groups in the public and private sectors should focus on to improve the quality of health care delivered to all Americans. The priority areas selected represent the entire spectrum of health care from preventive care to end of life care. They also touch on all age groups, health care settings and health care providers. Collective action in these areas could help transform the entire health care system. In addition, the report identifies criteria and delineates a process that DHHS may adopt to determine future priority areas.
Keywords: Health and Medicine

Leadership by Example: Coordinating Government Roles in Improving Health Care Quality - Institute of Medicine (The National Academies Press, 2003)
The federal government operates six major health care programs that serve nearly 100 million Americans. Collectively, these programs significantly influence how health care is provided by the private sector. Leadership by Example explores how the federal government can leverage its unique position as regulator, purchaser, provider, and research sponsor to improve care - not only in these six programs but also throughout the nation's health care system. The book describes the federal programs and the populations they serve: Medicare (elderly), Medicaid (low income), SCHIP (children), VHA (veterans), TRICARE (individuals in the military and their dependents), and IHS (native Americans). It then examines the steps each program takes to assure and improve safety and quality of care. The Institute of Medicine proposes a national quality enhancement strategy focused on performance measurement of clinical quality and patient perceptions of care. The discussion on which this book focuses includes recommendations for developing and pilot-testing performance measures, creating an information infrastructure for comparing performance and disseminating results, and more. Leadership by Example also includes a proposed research agenda to support quality enhancement. The third in the series of books from the Quality of Health Care in America project, this well-targeted volume will be important to all readers of To Err Is Human and Crossing the Quality Chasm - as well as new readers interested in the federal government's role in health care.
Keywords: Health and Medicine

Quality Through Collaboration: The Future of Rural Health - Institute of Medicine (The National Academies Press, 2005)
Building on the innovative Institute of Medicine reports To Err Is Human and Crossing the Quality Chasm, Quality Through Collaboration: The Future of Rural Health offers a strategy to address the quality challenges in rural communities. Rural America is a vital, diverse component of the American community, representing nearly 20% of the population of the United States. Rural communities are heterogeneous and differ in population density, remoteness from urban areas, and the cultural norms of the regions of which they are a part. As a result, rural communities range in their demographics and environmental, economic, and social characteristics. These differences influence the magnitude and types of health problems these communities face. Quality Through Collaboration: The Future of Rural Health assesses the quality of health care in rural areas and provides a framework for core set of services and essential infrastructure to deliver those services to rural communities. The book recommends: Adopting an integrated approach to addressing both personal and population health needs Establishing a stronger health care quality improvement support structure to assist rural health systems and professionals Enhancing the human resource capacity of health care professionals in rural communities and expanding the preparedness of rural residents to actively engage in improving their health and health care Assuring that rural health care systems are financially stable Investing in an information and communications technology infrastructure It is critical that existing and new resources be deployed strategically, recognizing the need to improve both the quality of individual-level care and the health of rural communities and populations.
Keywords: Health and Medicine

Improving the Quality of Health Care for Mental and Substance-Use Conditions - Institute of Medicine (The National Academies Press, 2006)
Each year, more than 33 million Americans receive health care for mental or substance-use conditions, or both. Together, mental and substance-use illnesses are the leading cause of death and disability for women, the highest for men ages 15-44, and the second highest for all men. Effective treatments exist, but services are frequently fragmented and, as with general health care, there are barriers that prevent many from receiving these treatments as designed or at all. The consequences of this are serious—for these individuals and their families; their employers and the workforce; for the nation's economy; as well as the education, welfare, and justice systems. Improving the Quality of Health Care for Mental and Substance-Use Conditions examines the distinctive characteristics of health care for mental and substance-use conditions, including payment, benefit coverage, and regulatory issues, as well as health care organization and delivery issues. This new volume in the Quality Chasm series puts forth an agenda for improving the quality of this care based on this analysis. Patients and their families, primary health care providers, specialty mental health and substance-use treatment providers, health care organizations, health plans, purchasers of group health care, and all involved in health care for mental and substance–use conditions will benefit from this guide to achieving better care.
Keywords: Health and Medicine

Keeping Patients Safe: Transforming the Work Environment of Nurses - Institute of Medicine (The National Academies Press, 2004)
Building on the revolutionary Institute of Medicine reports To Err is Human and Crossing the Quality Chasm, Keeping Patients Safe lays out guidelines for improving patient safety by changing nurses' working conditions and demands. Licensed nurses and unlicensed nursing assistants are critical participants in our national effort to protect patients from health care errors. The nature of the activities nurses typically perform – monitoring patients, educating home caretakers, performing treatments, and rescuing patients who are in crisis – provides an indispensable resource in detecting and remedying error-producing defects in the U.S. health care system. During the past two decades, substantial changes have been made in the organization and delivery of health care – and consequently in the job description and work environment of nurses. As patients are increasingly cared for as outpatients, nurses in hospitals and nursing homes deal with greater severity of illness. Problems in management practices, employee deployment, work and workspace design, and the basic safety culture of health care organizations place patients at further risk. This newest edition in the groundbreaking Institute of Medicine Quality Chasm series discusses the key aspects of the work environment for nurses and reviews the potential improvements in working conditions that are likely to have an impact on patient safety.
Keywords: Health and Medicine; Education

Crossing the Quality Chasm: A New Health System for the 21st Century - Institute of Medicine (The National Academies Press, 2001)
Second in a series of publications from the Institute of Medicine's Quality of Health Care in America project Today's health care providers have more research findings and more technology available to them than ever before. Yet recent reports have raised serious doubts about the quality of health care in America. Crossing the Quality Chasm makes an urgent call for fundamental change to close the quality gap. This book recommends a sweeping redesign of the American health care system and provides overarching principles for specific direction for policymakers, health care leaders, clinicians, regulators, purchasers, and others. In this comprehensive volume the committee offers: A set of performance expectations for the 21st century health care system. A set of 10 new rules to guide patient-clinician relationships. A suggested organizing framework to better align the incentives inherent in payment and accountability with improvements in quality. Key steps to promote evidence-based practice and strengthen clinical information systems. Analyzing health care organizations as complex systems, Crossing the Quality Chasm also documents the causes of the quality gap, identifies current practices that impede quality care, and explores how systems approaches can be used to implement change.
Keywords: Health and Medicine

Health Professions Education: A Bridge to Quality - Institute of Medicine (The National Academies Press, 2003)
The Institute of Medicine study Crossing the Quality Chasm (2001) recommended that an interdisciplinary summit be held to further reform of health professions education in order to enhance quality and patient safety. Health Professions Education: A Bridge to Quality is the follow up to that summit, held in June 2002, where 150 participants across disciplines and occupations developed ideas about how to integrate a core set of competencies into health professions education. These core competencies include patient-centered care, interdisciplinary teams, evidence-based practice, quality improvement, and informatics. This book recommends a mix of approaches to health education improvement, including those related to oversight processes, the training environment, research, public reporting, and leadership. Educators, administrators, and health professionals can use this book to help achieve an approach to education that better prepares clinicians to meet both the needs of patients and the requirements of a changing health care system.
Keywords: Education; Health and Medicine

Fostering Rapid Advances in Health Care: Learning from System Demonstrations - Institute of Medicine (The National Academies Press, 2003)
In response to a request from the Secretary of the Department of Health and Human Services, the Institute of Medicine convened a committee to identify possible demonstration projects that might be implemented in 2003, with the hope of yielding models for broader health system reform within a few years. The committee is recommending a substantial portfolio of demonstration projects, including chronic care and primary care demonstrations, information and communications technology infrastructure demonstrations, health insurance coverage demonstrations, and liability demonstrations. As a set, the demonstrations address key aspects of the health care delivery system and the financing and legal environment in which health care is provided. The launching of a carefully crafted set of demonstrations is viewed as a way to initiate a "building block" approach to health system change.
Keywords: Health and Medicine

To Err Is Human: Building a Safer Health System - Institute of Medicine (The National Academies Press, 2000)
Experts estimate that as many as 98,000 people die in any given year from medical errors that occur in hospitals. That's more than die from motor vehicle accidents, breast cancer, or AIDS—three causes that receive far more public attention. Indeed, more people die annually from medication errors than from workplace injuries. Add the financial cost to the human tragedy, and medical error easily rises to the top ranks of urgent, widespread public problems. To Err Is Human breaks the silence that has surrounded medical errors and their consequence—but not by pointing fingers at caring health care professionals who make honest mistakes. After all, to err is human. Instead, this book sets forth a national agenda—with state and local implications—for reducing medical errors and improving patient safety through the design of a safer health system. This volume reveals the often startling statistics of medical error and the disparity between the incidence of error and public perception of it, given many patients' expectations that the medical profession always performs perfectly. A careful examination is made of how the surrounding forces of legislation, regulation, and market activity influence the quality of care provided by health care organizations and then looks at their handling of medical mistakes. Using a detailed case study, the book reviews the current understanding of why these mistakes happen. A key theme is that legitimate liability concerns discourage reporting of errors—which begs the question, "How can we learn from our mistakes?" Balancing regulatory versus market-based initiatives and public versus private efforts, the Institute of Medicine presents wide-ranging recommendations for improving patient safety, in the areas of leadership, improved data collection and analysis, and development of effective systems at the level of direct patient care. To Err Is Human asserts that the problem is not bad people in health care—it is that good people are working in bad systems that need to be made safer. Comprehensive and straightforward, this book offers a clear prescription for raising the level of patient safety in American health care. It also explains how patients themselves can influence the quality of care that they receive once they check into the hospital. This book will be vitally important to federal, state, and local health policy makers and regulators, health professional licensing officials, hospital administrators, medical educators and students, health caregivers, health journalists, patient advocates—as well as patients themselves. First in a series of publications from the Quality of Health Care in America, a project initiated by the Institute of Medicine
Keywords: Health and Medicine